2017
DOI: 10.35627/2219-5238/2017-293-8-50-53
|View full text |Cite
|
Sign up to set email alerts
|

Mental State Students Teenagers: A Retrospective Analysis of the Prevalence Of Borderline Mental Pathology

Abstract: The comprehensive study included 128 adolescents aged 15-17 years, students of the pedagogical College and school sports, the obtained data compared with data from similar studies using standardized diagnostic approach, conducted in 1988 and 2003. Data on structure of boundary mental pathology and the addiсtion of disturbances, including information are provided. The conclusion about extremely adverse condition of mental health of teenagers of the surveyed contingent during 30 years and need of development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…In General, the frequency of this complaint increased significantly from 44.6% to 55.6% (p<0.05) for the entire cohort of observed students, which indicates the accumulation of fatigue throughout the day in students and insufficient night rest. Thus, the data from Table 1 shows an increase in the number of complaints among school children during the first 2 months of study, the accumulation of fatigue throughout the day in the observed school children and their insufficient night rest [1,13,17]. In addition, girls are much more likely than boys to present all the main complaints that indicate neurotic and asthenic reactions that develop in the course of educational activities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In General, the frequency of this complaint increased significantly from 44.6% to 55.6% (p<0.05) for the entire cohort of observed students, which indicates the accumulation of fatigue throughout the day in students and insufficient night rest. Thus, the data from Table 1 shows an increase in the number of complaints among school children during the first 2 months of study, the accumulation of fatigue throughout the day in the observed school children and their insufficient night rest [1,13,17]. In addition, girls are much more likely than boys to present all the main complaints that indicate neurotic and asthenic reactions that develop in the course of educational activities.…”
Section: Resultsmentioning
confidence: 99%
“…It was advisable to use a questionnaire to identify children's complaints. The survey of schoolchildren using a standardized questionnaire has a high sensitivity exceeding 80%, which is proved by scientific research [17,18,[20][21][22][23][24]. It should be noted that the questionnaire used is anonymous, it only indicates the gender and age of the child.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Человечество, вступив в третье тысяче летие, вместе с огромными достижениями в области технического прогресса приобрело новые источники страха [10]. Школьники в силу эмоциональной лабильности наиболее подвержены страхам, которые, накладываясь на традиционные детские фобии, могут приводить к серьезным нарушениям эмоциональной сферы вплоть до развития невротических расстройств [11][12] complaining of sleep disturbance, visual impairment and headaches became 2.7, 1.1, and 1.1 times higher during lockdown. We revealed significant differences in sleep disorders, headaches, dizziness, complaints of vision impairment, fatigue, and irritability between successful and unsuccessful schoolchildren (p < 0.05).…”
unclassified
“…Спилбергера (1983), трево га как состояние и тревожность как свойство личности представляют собой неприятное по своей окраске эмоциональное состояние или внутреннее условие, которое характеризуется субъективными ощущениями напряжения, бес покойства, мрачных предчувствий. Состояние тревоги возникает, когда индивид воспринимает определенный раздражитель или ситуацию как несущие в себе актуально или потенциально элементы опасности, угрозы, вреда [12]. Таким образом, увеличение в 1,4 раза числа тревожных школьников в период изоляции свидетельству ют о дестабилизации процессов социальной и психологической адекватности.…”
unclassified